A Study on the Heat Transfer Characteristics of Refrigerating Cabinet Gasket - Chen Qi; Yan Gang; Fang Zhongcheng; Yuan Baoli; Ren Wei (Zhileng xuebao)
Gasket is an important connection structure between refrigerator door and body, and heat transfer through gasket is an important component of refrigerator thermal load. Both CFD simulations and experimental test were carried out to analyze the heat transfer characteristics near gasket region. This paper primarily focuses on heat transfer paths and the proportions, which lays the foundation for the optimal design of gasket. The result shows that total thermal load of gasket is 2.2W, accounting for 5.5% of the total heat loss of a refrigerator, and thermal loads from gasket to refrigerating body and from gasket to refrigerating cabinet account for 41.56% and 45.07% of the total thermal load near the gasket region, respectively. Besides, the magnetic stripe is a key factor of the total thermal load of gasket. To reduce the width of gasket from 9.6mm to 8.4mm could effectively reduce the gasket thermal load from gasket to refrigerating body by 51.7%, resulting in a 21.1% reduction of total thermal load near gasket．